Effect Of Pre-Earthquake Disaster TrainingEarth About Wrapsing Splains Against Student/Student Knowledge Level At Sma Negeri 1 Pundong Bantul - Endah Tri Wulandari; Devi Anggita Cahyani; Gatot Suparmanto (Jurnal Kesehatan Kusuma Husada, 2025)
Earthquakes are one of the natural disasters which in reality cause quite a large impact, especially the number of victims caused. One location that has a fatal risk is school. In fact, school safety needs to be a global priority to face the threat of earthquake disasters. This negative impact is caused by a lack of knowledge and preparedness to anticipate an earthquake disaster. There is a need to increase preparedness to reduce the bad risks that may occur. Therefore, the aim of this research is to determine the effect of pre-earthquake disaster training regarding splint dressing on the level of knowledge of students at SMA N 1 Pundong. The method used in this research was pre-experiment. The research design used was a one-group pretest-posttest design. The research results showed that there was an Asymp.sig value. (2-tailed) 0.000, because the value of 0.000 is smaller than <0.05, it can be concluded that "Ha is accepted" which means there is a difference between the pretest and posttest results, so it can be concluded that there is an influence from the Pre-Earthquake Disaster Training on Wraps Bidai on Knowledge in Students and Students of SMA Negeri 1 Pundong.